PENGARUH LITERASI KEUANGAN, MOTIVASI, RETURN DAN RISIKO TERHADAP MINAT INVESTASI MAHASISWA DI PASAR MODAL - Hariyanto Hariyanto; Damayanti Damayanti (J-MACC, 2022)
This This study aims to prove the effect of financial literacy, motivation, return and risk on the investment interest of STIE YPPI Rembang students. The population used in this study was management students at STIE YPPI Rembang. The sample selection technique used proportional random sampling technique. The data analysis technique used multiple linear regression analysis. The results of this study indicate that financial literacy and motivation have no significant positive effect on student investment interest. While the return and risk variables have a significant positive effect on student investment interest. The value of Adjusted R2 is 0.601, it can be interpreted that 60.1% of the variation in student investment interest can be explained by variations of the four independent variables, namely financial literacy, motivation, return and risk. While the remaining 39.9% is explained by other reasons not examined in this study.